2013
DOI: 10.1016/j.matdes.2012.09.045
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of deformation mechanism and microstructure evolution during hot deformation of Ti–6Al–2Zr–1Mo–1V alloy

Abstract: a b s t r a c tIsothermal tensile tests have been performed to study the deformation mechanisms and microstructure evolution of Ti-6Al-2Zr-1Mo-1V titanium alloy in the temperature range 750-850°C and strain rate range 0.001-0.1 s À1. The deformation activations have been calculated based on kinetics rate equation to investigate the hot deformation mechanism. Microstructures of deformed samples have been analyzed by electron backscatter diffraction (EBSD) to evaluate the influences of hot deformation parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(23 citation statements)
references
References 31 publications
(61 reference statements)
1
22
0
Order By: Relevance
“…Furuhara et al [16] found the CDRX in the b phase of Ti-10V-2Fe-3Al during hot deformation. Moreover, the previous work [17,18] revealed that DRX played an important role in the a phase evolution of Ti-1.5Fe and Ti-6Al-2Zr-1Mo-1V during hot deformation. A few physical models have also been established so as to describe the DRX behavior [19,20].…”
Section: Introductionmentioning
confidence: 86%
“…Furuhara et al [16] found the CDRX in the b phase of Ti-10V-2Fe-3Al during hot deformation. Moreover, the previous work [17,18] revealed that DRX played an important role in the a phase evolution of Ti-1.5Fe and Ti-6Al-2Zr-1Mo-1V during hot deformation. A few physical models have also been established so as to describe the DRX behavior [19,20].…”
Section: Introductionmentioning
confidence: 86%
“…Recent researches indicate that the hot deformation mechanisms of titanium alloys, which are generally controlled by thermal activation, are not only influenced by alloying elements and initial microstructure, but also affected by deformation temperature, strain and strain rate [24]. The flow softening mechanism of two-phase titanium alloys varies with deformation conditions as well as initial microstructure.…”
Section: Flow Softening Mechanism Analysismentioning
confidence: 99%
“…Simultaneously, some tiny grains (<5 μm) without any LGBS appeared, which means the recrystallization was taken place. The tiny grains are connected with each other, which is termed as "necklace structure," a common result of the thermomechanical processing for two-phase Tialloys [31][32][33]. It should be noted that the schmid factor increased significantly.…”
Section: Microstructural Evolutionmentioning
confidence: 99%